Credit Suisse : how a global financial services firm became 'One Bank' - Mitkowski, Allison, (SAGE knowledge. Cases., 2016)
As he surveyed the Credit Suisse Group in 2004, CEO Oswald J. Gru?bel saw a far-flung financial services firm that offered a variety of excellent products and services, but did not have much coordination between its divisions. The Credit Suisse Group was comprised of two flagship banks that operated as loosely-coupled entities. The company's investment banking division, Credit Suisse First Boston (CSFB), was based in the United States, whereas the Credit Suisse private bank was headquartered in Zurich. The physical separation symbolized a deeper divide that had inhibited cooperation. Gru?bel believed that the business units were not capitalizing on obvious cross-division business opportunities and therefore were ceding business to its rivals. This case study analyses this topic.